Analysis of the design and technological process of grain cleaning machines operating on pneumatic fractional technology (review) - A. L. Glushkov (Аграрная наука Евро-Северо-Востока, 2025)
Fractionation of grain heap at the pre-cleaning stage reduces the total energy consumption for grain processing and its injury by reducing the number of cleaning operations required to obtain high-quality seed material. The purpose of the review is to analyze the design and technological process of grain cleaning machines operating on the pneumatic fractional technology in order to identify promising areas of research in this field. It was found that grain pneumatic separators have a simple design and high productivity, which does not depend on the contamination and humidity of the source material. However, their use in the preliminary cleaning mode is limited due to the low effect of cleaning grain from coarse and fine impurities due to the lack of appropriate sieve working bodies. Universal air-sieve grain cleaning machines are used to separate grain into fractions by air flow. These are high-performance double-aspiration machines, the first aspiration of which separates light impurities from the processed material, and the second removes the forage fraction, which includes puny, crushed and biologically defective grain. The use of these machines in the pre-cleaning mode will reduce grain injury, since after separation of the forage fraction, a cleaner material is obtained at the outlet, requiring fewer operations for further cleaning. When developing new air systems for grain pre-cleaning machines operating on the pneumatic fractional technology, it is necessary to take into account the use in their design of: cross flow fans, since they are well combined with other elements and create a uniform air flow across the entire width, which has a positive effect on the efficiency of material separation; aspiration channels with a developed lower part and optimal parameters corresponding to their specific load, contribute to achieving maximum efficiency in separating light impurities and forage grain. The separation of the forage fraction from grain before cleaning on sieves reduces the load on the sifting and grading sieves and improves the quality of the cleaned material at the outlet.